2014
DOI: 10.1515/jcim-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Practices and attitudes toward complementary and alternative medicine in inflammatory bowel disease: a survey of gastroenterologists

Abstract: Academic IBD specialists were receptive to the use of CAM, and most felt that it had a role in the treatment of IBD, without necessarily compromising conventional therapy. Formal educational initiatives and societal recommendations on the use of CAM may facilitate a more systematic approach to its use in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A qualitative study by Lindberg et al suggested that IBD patients would like to discuss CAM use with their physician, but they do not initiate any conversation on this subject for fear they would not be taken seriously [35]. In contrast, gastroenterologists were shown to have a generally positive attitude regarding CAM: a study from Gallinger and Nguyen based on a web survey reported that 68% of gastroenterologists believed that CAM could be a good adjuvant in IBD therapy and 72% felt comfortable discussing it [36]; a qualitative study by Lindberg et al reported that health professionals believed CAM belonged within healthcare and was relevant to conventional therapeutics [37]. Notwithstanding, a common complaint among all gastroenterologists and other health professionals was the lack of formal knowledge in the area.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study by Lindberg et al suggested that IBD patients would like to discuss CAM use with their physician, but they do not initiate any conversation on this subject for fear they would not be taken seriously [35]. In contrast, gastroenterologists were shown to have a generally positive attitude regarding CAM: a study from Gallinger and Nguyen based on a web survey reported that 68% of gastroenterologists believed that CAM could be a good adjuvant in IBD therapy and 72% felt comfortable discussing it [36]; a qualitative study by Lindberg et al reported that health professionals believed CAM belonged within healthcare and was relevant to conventional therapeutics [37]. Notwithstanding, a common complaint among all gastroenterologists and other health professionals was the lack of formal knowledge in the area.…”
Section: Discussionmentioning
confidence: 99%
“…According to a Canadian survey (23), 70% of patients indicated that they have talked to their physician about complementary and alternative medicine. On the other hand, 65% of gastroenterologists state that they do not have formal training in complementary and alternative medicine and 55% do not have a systematic approach to discussing these topics (24). Interestingly, alternative medicine and exercise were topics that also scored among the lowest in quality and availability of information; the information need, therefore, appears not to be met appropriately.…”
Section: Figure 4) Quality and Availability Of Information And Level mentioning
confidence: 99%
“…Communication between healthcare professionals and patients is essential, yet it seems that a ‘ don't ask – don't tell ’ scenario is common, whereby clinicians do not actively seek information and patients do not voluntarily disclose it . Reasons for clinicians failing to inquire includes poor awareness of CM safety issues, a belief that few of their patients take CM, lack of confidence in dealing with this subject, or an assumption that information will be volunteered unsolicited . For some, there is the perceived threat that by respecting the patient's choice to use an unproven CM, the principles of evidence‐based medicine will be undermined and the patient will mistake this for endorsement .…”
Section: Discussing CM Use With Patientsmentioning
confidence: 99%
“…26 Other recent surveys of medical practitioners outside of Australia include surveys of different types of doctors in Germany, 28 paediatricians in the Netherlands, 29 GP in North West England 30 and gastroenterologists in the United States. 31 These surveys found that a significant proportion of medical practitioners consider there is a role for CM in their clinical practice, and many prescribe CM or refer patients for a limited range of CM interventions.…”
Section: Doctors' Perceptions and Use Of CMmentioning
confidence: 99%
See 1 more Smart Citation